Note on fractional Mellin transform and applications - Kilicman, Adem; Omran, Maryam (SpringerOpen, 2016)
In this article, we define the fractional Mellin transform by using Riemann–Liouville fractional integral operator and Caputo fractional derivative of order α≥0 and study some of their properties. Further, some properties are extended to fractional way for Mellin transform.